Jezebel's voice : a feminist reconstruction of the message to Thyatira in the Book of Revelation - Shier, Sarah Elizabeth (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2011)
Although she reportedly describes herself as a prophetess, the voice of the woman whom the Book of Revelation’s misogynistic Son of Man pejoratively describes as “the Woman Jezebel” (Rev 2:20) has been silenced by its author. The Introduction to this study notes that the only clue to “Jezebel’s” prophetic words is provided by the description of her teaching as being “the deep things of Satan” (Rev 2:24). In order both to discover the nature of her teaching and to allow her lost prophetic voice to speak again, this study aims to reconstruct the message to Thyatira (Rev 2:18-29) and the conflict contained within it (Rev 2:22-23) between the Son of Man (Rev 1:13), in his persona of the Son of God (Rev 2:18), from the point of view of the Prophetess of Thyatira. In order to carry out these aims, a review is made in Chapter 1 of feminist critiques of the presentation of the Woman Jezebel, of the Son of Man as a gendered character and of the conflict between the two characters. This review concludes that there is a lack of feminist interpretation in all three areas, in particular in the reconstruction of the conflict. In Chapter 2 the methodology by which such an interpretation may be made is reached by taking into account the necessary strategic criteria and the difficulties of interpretation posed, firstly, by the vocal hierarchy of the first three chapters of Revelation and, secondly, by the Woman Jezebel being both a historical woman and a character in the Book of Revelation. This methodology is one of feminist comparative analysis using a hermeneutics of suspicion and transformation, which considers the presentation of the characters and the conflict in both their socio-historical and literary contexts. The consideration of the socio-historical background to the conflict in the first-century C.E. trading city of Thyatira undertaken in Chapter 3 takes into account a variety of possible causes of the conflict, including the author of Revelation’s belief in magic and the Prophetess’s female gender. Interpretations are then made in the following two chapters of the presentations of the two adversaries in the conflict. These interpretations analyse in turn the Son of Man in his persona of the Son of God and the Woman Jezebel, the Prophetess of Thyatira, in their socio-historical and literary situations.
Keywords: Religions, Peace Studies & Theology, Ph.D.; Ph.D. Trinity College Dublin.